Reproduksi Kekuasaan Kyai Dan Blater Di Kabupaten Bangkalan - Abdussalam, Ishaq (DIMENSI, 2015)
In Madurese culture, Kiai symbolizedas someone who has adeep knowledge of religion, he is also believed as a representative prophet on earth. Discourse knowledge saminawa athoâna is a manifestation of how the figure of Kiai has a sacred meaning for the people of Madura, so that the words and actions become apatron who always followed by the public. While Blater pointing to things that dimension of violence, carok is the domain that cannot be separated with the blater. For those carok is the best way to go if their self-esteem feels to be harassed. So this blater group respected by the community and tend tobe feared because of the courage and strength.Kiai and blater in local politics of Madura are often used as a means of seizing power. This study seeks to unpack the phenomenon, such as: want to reveal the use of symbols of religious ideology (kiai) as a strategy to influence and attract the sympathy of the masses in Bangkalan elections 12-12-2012, and uncover strategies of blater is meas power presses and organizing the masses in Bangkalan elections.This study uses a critical paradigm approach to dismantle the relations of the power that inherent in the reality studied. Critical paradigm was chosen because it is believed that the reality of the struggle for power in Bangkalan elections involves cultural and political power and the economy. This paradigm always sees that reality for med over these relations.The results of this study are: a) all the symbols and identities attached to kiai used as a strategy for hegemony community by Bangkalan regent candidates. The candidates fight the owner of kiai Kholil identity to attract the sympathy of the masses, because they still have a blood descendant of kiai Kholil that was very influential in Bangkalan. b) The relation of kiai-students is an effective means of gaining support from the district level till to the villages. c) While blaterisme strategy covers two things. First, structural blaterisme and the Second, blaterisme non-structural.